(untitled) (International Journal of Engineering and Computer Science, 2015)
In a rapidly changing technological environment, though the Local Area Network helps an organization gain a competitive edge, both domestically and internationally, but due to the fast changing technology, the environment of organizations, and the growing role of information is challenging firms both large and small to replace their copper-based networks with fiber optics. Fiber-based Passive Optical LAN (POL) technology is a point-to-multipoint network architecture optimized for local area network (LAN) environments to provide a fiber-to-the-desktop solution. (1) and has emerged as a particularly promising alternative for enterprises in need of a secure, converged network with increased bandwidth. Passive optical LAN (POL) technology platforms optimized for enterprise LAN environments have become available only in the last couple of years. Therefore in this paper authors have summarizes the potential use of POL for further use. We’ll then discuss traditional LAN architecture, Passive Optical LAN components and further implications on network management, real estate, and energy consumption.